STUDY FOR DOMINANCE AND NUTRITION OF WEEDS AS FEED IN VARIOUS CROP LAND IN YOGYAKARTA - Suwignyo, Bambang (2016)
The study aimed to determine the dominant species and nutrient content of weeds as feed on a variety of agricultural land in Yogyakarta. Observations were done on of paddy fields,corn,beans and vacant land of Pakem upperland area (621 m asl), as well as paddy fields, chili and vacant land Samas lowland area (10 m asl), three area each. The research was conducted in September-October 2015. The observations was done include measurement of dominance, plant identification and quality of weed. Dominance of weed was measured by using line intercept transect technique. Sample weed identification and quality examination (proximate) was done at the Laboratory of Forage and Pasture Science, Faculty of Animal Science UGM. Results showed that dominant of weeds in the lowland for shrub type were Phyllantus amarus,Commelina benghalensis,Ludwigia octovalvis and Portulaca oleracea while the type of grass were Leptochlo achinensis, Eleusinei ndica, Cyperus compressus, Paspalumdistichum and Brahiariamutica Dominant of weeds in the upperland for shrub type were Ageratum conyzoides,Eclipta alba,Ludwigia octovalvis,Cleome rutidosperma and Portulaca oleracea for type of grass were Digitaria setigera,Eleusine indica,Cyperus iria,Echinochoa oryzides and Fimbristylismiliacea . Thus, found three dominant of weeds with quality of DM and OM respectively Ludwigia octovalvis (18,76%90,95%), Portulaca oleracea (8,09%76,70%) and Eulisine indica (20,67%88,38%).